Implementasi Kebijakan Perbub Diniyah Kabupaten Pasuruan Untuk Meningkatkan Mutu Pendidikan Di Program Tahfidz Tpq Al-Ihsan Lebak Pasuruan - Zahro', Fatimatuz; Ma'arif , Syamsul; Sahudi, Sahudi (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to analyze the implementation of the Diniyah Regent's Regulation (Perbub) regarding Compulsory Diniyah Madrasah Study in Pasuruan Regency, with a focus on improving the quality of education in the Tahfidz TPQ Al-Ihsan Program, Lebak Pasuruan. This regulation provides a legal basis for the implementation of religious education and aims to improve the quality of religious education through programs such as tahfidz Al-Qur'an. The research uses qualitative methods with observation, interview and documentation techniques. This research evaluates the implementation of the Diniyah Regent Regulation (Perbup) in Pasuruan Regency, especially in the Tahfidz Program at TPQ Al-Ihsan. The research results show that this Perbup plays an important role in improving the quality of religious education by providing a structured legal and operational framework. TPQ Al-Ihsan has succeeded in adapting this policy through developing an integrated curriculum that combines religious learning and general education, as well as implementing dynamic teaching methods that are updated regularly. Even though there is ongoing training for teachers, challenges related to teacher qualifications, student attendance, and parental support are still obstacles. The implementation of learning is carried out in a structured manner with a gradual approach, however the evaluation shows the need for improvement in several aspects to optimize the results of tahfidz education and religious education as a whole. This research emphasizes the importance of collaboration between the community, parents and other stakeholders in supporting the success of the Diniyah program at TPQ Al-Ihsan.